Maximization of soybean exploration. I. Effects of the cut-off at 60 days in the production of hay and yields from regrowth - Rezende, Pedro Milanez de (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out in a dystrophic Dusky Red latosol at Lavras, MG, to study the capacity of ten soybean Glycine max (L.) Merrill cultivars to produce hay, and grain yield from regrowth. The experimental design was a randomized block with 20 treatments and four replications. The treatments were: 'UFV-1', IAC-2', 'UFV-2', IAC-5', 'UFV-3', ‘santa Rosa', IAC-3', 'TK-5', 'Majos' and ‘Bossier' cut at 20 cm height at 60 days after planting, and same cultivars without cutting (check). The soybean hay is quite similar to alfalfa hay as far as chemical composition is concerned. 'IAC-5' and 'IAC-3' showed the best productions of fresh matter, hay, and dry matter. In general, the checks showed good grain yield, and 'Majos', 'Santa 'Rosa' and ‘IAC-5' were the best with 2,104 kg/ha, 2,094 kg/ha and 2,072 kg/ha, respectively. The grain yields from regrowth were affected by a dry weather period during, and after the cutting operation. The grain yields of 'Bossier' and 'UFV-2' were 41.06% and 36.06% respectively, of the check. The others were lower than 36.06% of it. The cut plants showed lower plant height, first pod height and lodging than the check.